Faktor-faktor yang Mempengaruhi Terjadinya Kecenderungan Kecurangan (Fraud) pada Lembaga Perkreditan Desa Kecamatan Kuta Selatan - Listyanti, Ni Kadek Intan Karunia; Sukartha, P. D’yan Yaniartha; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 34 No 6 (2024)DO - 10.24843/EJA.2024.v34.i06.p13, 2024)
The purpose of this research was to examine the effect of the effectiveness of internal control, religiosity, ethical behavior, and whistleblowing to fraud tendencies. This research was conducted at t LPD in South Kuta District, totaling 9 LPDs with a total of 86 employees as respondents. Purposive sampling technique is used as a technique in sampling using a questionnaire. The findings of this study are that the effectiveness of internal control, religiosity, and ethical behavior partially had a negative effect on the fraud tendencies, while whistleblowing had no effect on the fraud tendencies. This research provides input and considerations for the leadership of the South Kuta District LPD which are expected to increase the effectiveness of internal control, religiosity, ethical behavior, and implement whistleblowing to prevent the occurrence of a tendency of fraud. Keywords: Internal Control Effectiveness; Religiosity; Ethical Behavior; Whistleblowing; Fraud Tendencies.